Anaesthetists practice of intra-operative fluid management in the paediatric population in three academic hospitals - Bruckmann, Klaudia Lmiolo (My University, 2018)
Background. Peri-operative fluid management in paediatric surgical patients is an integral part of any anaesthetic and influences surgical outcome. This study assesses the practice of peri-operative paediatric fluid administration in the Department of Anaesthesiology. Method. This prospective descriptive cross-sectional practice-based study used an anonymous self-administered questionnaire to assess the approach to fluid administration during the peri-operative period in the paediatric population by the anaesthetists at Wits. A total of 125 completed questionnaires were received which attained a 61.3 % response rate. The questionnaire aimed to assess the approach to intra-operative fluid administration in both stable and unstable paediatric patients, knowledge of existing guidelines concerning peri-operative paediatric fluid administration, the approach to managing blood glucose intra-operatively and whether demographics, experience, training and designation influenced practice. Results. Only 54.4% of the department knew of a recognized and published paediatric fluid protocol. Experience (p= 0.0856), training (p=0.2016) and designation (p= 0.2915) had no influence over the use of a specific formula for fluid calculation in paediatric patients. The two most commonly used formulae for maintenance was the 2:1:0.5 rule used by 38.7% and the 4:2:1 rule used by 37.1% of the study population. The majority of participants used a balanced crystalloid solution when administering intra-operative maintenance fluid but 13.7% still used hypotonic solutions. There was no clear preference between crystalloids (50.8%) and colloids (45.2%) when treating a haemodynamically unstable paediatric patient, specialists were however significantly more likely to use a colloid for resuscitation when compared to non-specialists (p=0.003). Conclusion. This study revealed that there is no standard guideline when prescribing paediatric fluid intra-operatively at the Department of Anaesthesiology at Wits. Some anaesthetists practice unsafe fluid administration. Departmental guidelines do not exist and there should be a framework for safe practice put in place.
A research report submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of Anaesthesiology Johannesburg 2018
Keywords: Anesthesia; Anesthetics; Anesthetics--Pharmacology